Our knowledge of the internal world - Stalnaker, Robert (Oxford : Oxford University Press, 2008)
Robert Stalnaker opposes the traditional view that knowledge of one's own current thoughts and feelings is the unproblematic foundation for all knowledge. He argues that we can understand our knowledge of our thoughts and feelings only by viewing ourselves from the outside, by seeing our inner lives as features of the world.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Knowledge, Theory of